Biomechanical Analysis of the System “External Fixation Device – Bone” Behavior at the Stages of Tibial Diaphyseal Fracture Healing - Lazarev, I.A.; Radomskyi, O.A.; Ryzhkov, B.S.; Schultheiss, U.; Dendorfer, S.; Skyban , M.V. (TERRA ORTHOPAEDICA, 2025)
Summary. The use of external fixation devices for the treatment of diaphyseal fractures of the tibia has become the standard. However, most external fixation device (EFD) modifications have insufficient stiffness. Therefore, there is a need to develop an EFD design that could provide early limb loading with an optimal range of interfragmentary motion. A related challenge lies in determining the strength of bone regeneration during fracture healing, which cannot be objectively assessed in a clinical setting. However, these values can be calculated using the Finite Element Method (FEM).Objective. The objective of our work was to study the biomechanical behavior of the proposed “External Fixation Device – Tibia” system at the stages of bone regeneration under the condition of its loading by body weight using the FEM.Material and Methods. A computer simulation was carried out, at the initial stage of which a semi-full-scale prototype of the “External Fixation Device – Tibia” bone fragments fixation system was developed. Based on it, the next step was to create solid 3D models of the tibia and the EFD using the SolidWorks software package (Dassault, France). The EFD design used in the work consisted of 4 semi-rings (160 mm), 9 connecting beams (150 mm), two through pins (5 mm), 2 spongiosis screws (5 mm), 2 cortical screws (5 mm), and 6 clamps. All the components of the EFD were made of AISI320 stainless steel.Results and Discussion. Simulation computer modeling of the fixation capabilities of the proposed EFD showed that its stiffness is sufficient to provide a controlled load on the damaged limb within 20-24% of body weight from the first days of formation of granulation cartilage regenerate. It should be noted that the supporting function of the fibula is restored within 5-6 weeks after its fusion and is approximately 17-30% of the body weight. Therefore, in general, a controlled load on the limb can reach 50% of the body weight after 6 weeks of treatment. Subsequently, when mature bone tissue is formed around the fracture (most often within 8-17 weeks), the load on the limb can reach 130% of the body weight, which ensures the patient’s movement without additional support.Conclusions. The performed computer simulation modeling makes it possible to determine the behavior of the biomechanical environment of the proposed “External Fixation Device – Bone” system and allows to establish the amouth of limb loading in the process of developing a scientifically based rehabilitation program to create optimal conditions for fracture healing. The proposed design of the EFD can be used for the final treatment of diaphyseal fractures of the tibia and provides for the possibility of early loading on the “External Fixation Device – Bone” system.